Assessment of semi-active friction dampers. (15th September 2017) - dos Santos, Marcelo Braga; Coelho, Humberto Tronconi; Lepore Neto, Francisco Paulo; Mahfoud, Jarir
Highlights: Friction dampers are used as a semi active device in suspensions of vibratory. Five control laws had been study to modulate the normal force in friction dampers. The mean resonant peak attenuation was of 30 dB. Two strategies eliminate the resonant peaks of the vibratory systems. Had been proposed a figure of merits to classify the control laws performances. The proposed friction damper is efficient to reduce the vibration of N-DOF systems. Abstract: The use of friction dampers has been widely proposed for a variety of mechanical systems for which applying viscoelastic materials, fluid based dampers or other viscous dampers is impossible. An important example is the application of friction dampers in aircraft engines to reduce the blades' vibration amplitudes. In most cases, friction dampers have been studied in a passive manner, but significant improvements can be achieved by controlling the normal force in the contact region. The aim of this paper is to present and study five control strategies for friction dampers based on three different hysteresis cycles by using the Harmonic Balance Method (HBM), a numerical and experimental analysis. The first control strategy uses the friction force as a resistance when the system is deviating from its equilibrium position. The second control strategy maximizes the energy removal in each harmonic oscillation cycle by calculating the optimal normal force based on the last displacement peak. The third control strategy combines the first strategy with the homogenous modulation of the friction force. Finally, the last two strategies attempt to predict the system's movement based on its velocity and acceleration and our knowledge of its physical properties. Numerical and experimental studies are performed with these five strategies, which define the performance metrics. The experimental testing rig is fully identified and its parameters are used for numerical simulations. The obtained results show the satisfactory performance of the friction damper and selected strategy and the suitable agreement between the numerical and experimental results.